ASSESSMENT OF TRANSMITTED SPEECH SIGNAL DEGRADATIONS IN RICIAN AND RAYLEIGH CHANNEL MODELS - Zegarra Rodriguez, Demostenes; Jordane da Silva, Marielle; Mendes Silva, Francisco José; Brandão Junior, Luiz Carlos (INFOCOMP Journal of Computer Science, 2018)
Telecommunications services monitoring is of paramount importance, network operators must meet the expectations of their subscribers. On wireless communications, transmitted signal may suffer different degradations in the transmission channel. In the literature, there are different models of wireless channels, among the most cited are the Rician and Rayleigh fading channel models, each one presents different characteristics of transmission. In the speech quality assessment research area, most of the works focused on wired network type degradations, using parameters as packet losses, delay and jitter; however, wireless degradation characteristics are not considered. In this context, the present paper investigate the impact of different Doppler frequency shifts (Hz) on speech communications, using the fading channel models previously mentioned, and different multipath delay profiles. Performance evaluation parameters are based on the voice quality assessment algorithms described in recommendations ITU-T P.563 and P.862. The experimental results show how the variation range of the Doppler shift is related to speech quality index.